Disrespect and abuse during childbirth in East Hararghe Zone public health facilities, eastern Ethiopia: a cross-sectional study - Usso, Ahmedin Aliyi; Adem, Hassen Abdi; Alemu, Addisu; Mohammed, Aminu (Frontiers in Global Women's Health, 2023)
Background: Compassionate respectful maternity care during childbirth has been identified as a potential strategy to prevent and reduce maternal mortality and morbidity. Despite its importance, there is a paucity of information on the level of disrespect and abuse in eastern Ethiopia. This study assessed the level of disrespect and abuse during childbirth and associated factors among women who gave birth in East Hararghe public health facilities in rural eastern Ethiopia. Methods: A cross-sectional study was conducted among 530 women who gave birth in 20 East Hararghe public health facilities from April 1-30, 2020. Data were collected using a validated questionnaire. Bivariable and multivariable binary logistic regression analyses were employed to identify factors associated with disrespect and abuse during childbirth. The adjusted odds ratio (AOR) (95% CI) was used to report association, and statistical significance was set at P<0.05. Results: Overall 77% (95% CI: 73%, 81%) of women reported at least one type of disrespect and abuse during childbirth in East Hararghe public health facilities. In this study, average monthly income of fewer than 57.22 USD (AOR=2.29, 95% CI: 1.41, 3.71), being greater than 30 minutes away from a nearby health facility (AOR= 2.10 95% CI: 1.30, 3.39), not attending antenatal care (AOR=4.29, 95% CI: 2.17, 8.52), and giving birth during the nighttime (AOR=2.16, 95% CI: 1.37, 3.41) were associated with at least one type of disrespect and abuse during childbirth. Conclusion: More than three in every four women who gave birth in East Hararghe public health facilities were disrespected and abused during childbirth. Encouraging all pregnant women to attend antenatal care visits and improving the quality of health care service during the nighttime in all health facilities would be essential for preventing and reducing disrespect and abuse and its negative consequences.